Analisis Kualitas Website Menggunakan Metode Webqual dan Importance Performance Analysis (IPA) Pada Website Pondok Pesantren Al-Hidayah Pringsewu - Yusra Fernando; Catur Apriyani; Donaya Pasha; Dedy Alamsyah (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
The web has turned into an inseparable part of human existence in this computerized age. With the web, all the ideal data can be obtained effectively and quickly. However, the quality of the website needs to be evaluated to improve the information provided by the website. The purpose of this study was to analyze the quality of the website of the Al-Hidayah Islamic Boarding School. Website quality analysis using the Webqual method is a measurement of website quality based on end user perceptions and Importance Performance Analysis (IPA) is a technique for identifying the quality measurement attributes of the product. Based on the results of the Webqual Index calculation on the Al-Hidayah Islamic Boarding School website, it can be seen that the service interaction dimension gets the highest index value. While the information dimension (information) gets the lowest index value. Then the Importance Performance Analysis on the website there are several attributes that are in quadrant I which are the main priority for improving the quality of the website to increase user satisfaction, the information dimension is an indicator of timely information, relevant information. In the service interaction dimension, it is a safe indicator of personal information, feature facilities can be accessed properly, thus providing easy input or suggestions for the school.